pDNA capture using grafted adsorbents - Singh, Naveen Kumar (2018)
BACKGROUND: ‘Expanded’ composite materials are of interest as an alternative, or as a supplement, to packed-bed chromatography during bioproduct recovery and purification. Functionalized non-woven fabrics and mega-porous bodies are examples of systems that showed promise. However, there is scarce information on their suitability to capture and release plasmid DNA (pDNA), an important type of product employed in gene therapy. RESULTS: Composite adsorbents were prepared using either chemical (CG-DEAE-NW) or gamma-irradiated graft-polymerization (GIR-DEAE-MP), and subsequently modified to have diethylamino ethanol (DEAE) functionality. Capture experiments showed that pDNA can actually reversibly bind to the two mentioned adsorbents, with capacity values of 2.4 and 1.3 mg per mL, respectively. These values are in the range of what can be expected from commercial beaded adsorbents but lower that the values expected from monoliths. CONCLUSIONS: Expanded materials, due to their high voidage, may present limited capacity for pDNA. However, such materials are able to bind proteins and other contaminants from bacterial lysate, opening the way for their utilization in the ‘negative’ mode.